The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.18388/abp.2002_3830
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of nitric oxide on human hematological malignant cells.

Abstract: We investigated the cytotoxic effect of nitric oxide (NO) on primary culture of human hematological malignant cells. Sodium nitroprusside (SNP), an NO donor, had cytotoxic effects on the cells of some patients with malignant lymphoma (ML), acute myelocytic leukemia (AML) or chronic myelomonocytic leukemia (CMMoL), but not with multiple myeloma. Cultured cells from the ML patient remained sensitive to SNP after the cells became resistant to anti-cancer drugs. In contrast, the cells from the patients with AML an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The NO and NO‐related species have delineated antiproliferative, cytotoxic, and apoptotic effects of NO on several tumor cells, including leukemia, pancreatic, hepatic, and colon cancer (16–19). Although recently studies demonstrated NO‐induced apoptotic effects on oral cancer cells (20, 21), comparative effects of proliferation and differentiation on oral immortalized vs. malignant keratinocytes cells towards NO was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The NO and NO‐related species have delineated antiproliferative, cytotoxic, and apoptotic effects of NO on several tumor cells, including leukemia, pancreatic, hepatic, and colon cancer (16–19). Although recently studies demonstrated NO‐induced apoptotic effects on oral cancer cells (20, 21), comparative effects of proliferation and differentiation on oral immortalized vs. malignant keratinocytes cells towards NO was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…18 A therapeutic of particular interest for the treatment of lymphatic-related diseases is nitric oxide (NO), an extremely promiscuous signaling molecule that takes part in a variety of physiological processes ranging from vasodilation, [19][20][21][22][23] to neural signaling, 24 to immune cell cytotoxic defenses. [25][26][27][28] Because of the important role that NO plays in multiple physiological processes, there have been many attempts at modulating NO for therapeutic purposes. For example, NO delivered in the form of nitrate is used to control pain from angina, a disease affecting nine million people in the US with 500,000 new cases every year, and has been found to annually cost the healthcare system around $1.9 billion.…”
Section: Introductionmentioning
confidence: 99%
“…33 NO has also been explored for the treatment of various cancers, including lymphoma where a variety of NO donors have been shown to be chemosensitizers [34][35][36] as well as exhibit direct cytotoxicity. 25,[36][37][38][39] Despite the versatility of NO as a potential therapeutic in a broad array of pathologies, several challenges exist with utilizing NO for lymphatic-related therapy. First, NO participates in many interrelated physiological processes that each have different requirements for NO signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations